Overdiagnosis in sports medicine - de Vos, R.-J. (ASPETAR Sports Medicine Journal, 2017)
Overdiagnosis is defined as the identification of an `abnormality` that will never cause symptoms or death during an individual`s lifetime1. Overdiagnosis can be a side effect of screening for early forms of disease, but it is also observed in establishing a diagnosis after injury or evaluation of a recovery process after injury. Screening or measurements of diagnosis or recovery can be helpful in many cases, but may also have limitations and result in disadvantages for the individual being tested. Overdiagnosis occurs when an abnormality or disease is diagnosed correctly, but the abnormality or established diagnosis is irrelevant. This may result in harm for the tested individual if: